Handbook of art and global migration: theories, practices, and challenges - Dogramaci, Burcu; Mersmann, Birgit (De Gruyter, 2019)
Frontmatter -- CONTENT -- Art and Global Migration. Theories, Practices, and Challenges / Dogramaci, Burcu / Mersmann, Birgit -- Migratory Challenges for Art Production and Art History -- Toward a Migratory Turn / Dogramaci, Burcu -- From Global Turbulences to Spaces of Conviviality / Papastergiadis, Nikos / Trimboli, Daniella -- The Migrant Image / Nail, Thomas -- Immigrants, Refugees and the Arts / Martiniello, Marco -- Aesthetics and Art Practices of Migration -- Close Encounters / Bal, Mieke -- Fuocoammare and the Aesthetic Rendition of the Relational Experience of Migration / Dasgupta, Sudeep -- Paths Walked Twice / Gutberlet, Marie-Hélène -- Women, Art, Migration and Diaspora / O'Neill, Maggie -- Migratory Networks. Objects and Actors on the Route -- On Nomadic Textile Forms - The Aesthetic of Nomadic Textiles / Haehnel, Birgit / Reichstein, Sascha -- Cosmopolitan Nodes and Vectors / Lee, Rachel -- Photodocumentaries of Global Migration / Mersmann, Birgit -- Climates of Displacement / Demos, T. J. -- Places, Spaces, and Boundaries of Migration -- The Place of Faith / James-Chakraborty, Kathleen -- The Migratory Living Room / Dogramaci, Burcu -- Of Inner Cities and Outer Space / Pinther, Kerstin -- Histories and Memories of Migration -- Memory. Belonging. Engaging. / Bublatzky, Cathrine -- Migration, Dispossession, Post-Memorial Recuperations / Juneja, Monica -- Migration on Display / Ulz, Melanie -- Exhibiting Voids / Lanz, Francesca / Whitehead, Christopher -- Beyond Migration. Post-migratory Concepts and Strategies -- When Migration Turns from the Spectacular to the Ordinary / Moslund, Sten Pultz -- Migration and Postmigration as New Frameworks for Art Theory / Petersen, Anne Ring -- Postmigrant Practices of Living as Resistance / Yildiz, Erol -- The Postmigrant Condition in Fashion, Culture and Fashion Theory / Gaugele, Elke -- IMAGE CREDITS -- BIOGRAPHIES OF THE AUTHORS -- INDEX
Keywords: Aufsatzsammlung; Migration; Globalisierung; Kunst